Does the neighborhood context explain attitudes toward immigration? A study of opinions on immigration in the city of Turku, Finland - Staffan Himmelroos; Mikko Leino (Turun korkeakoulujen yhteiskunnallistaloudellinen tutkimusyhdistys ry., 2022)
The aim of this study is to find out if or to what extent residential context can explain attitudes toward immigration. Although immigration is a global phenomenon, the practical challenges related to integration need to be solved locally. For integration to succeed, the majority pop- ulation needs to accept the influx of new and different cultures as part of a common society. Against this background, it is important to understand the basis of different opinions on im- migration and how they are dispersed in the local community. We make use of large data set (n=2977) on attitudes toward immigration in Turku collected in 2012. It allows us to analyze how attitudes toward immigration vary within different parts of the municipality and whether neighborhood context can explain attitudes toward immigration. We find that the most potent explanation related to residential context is the general sentiment toward immigration in a neighborhood.